Numerical simulation of the tsunami of Camaná - Jiménez, César (2010)
On 23 June 2001, at 15:33 local time, the Camana city and all the Peruvian southern region were hit by a strong earthquake of magnitude 8.4 Mw and maximal intensity VIII in Mercalli scale. The epicenter was located on the sea in the forefront of Ocoña (Arequipa). Fifteen minutes later, a localized tsunami was generated, which destroyed the seaside town of Camana and caused the death of 24 people an 62 missing people. This event is the objet study through numerical simulations implementing the TIME model for tsunamis, the results obtained are the arrival time, the run up (maximal height of flooding), synthetic tidal gage recording and flooding maps, which will